Studi Kasus SDGs 4.4.1: Kemampuan ICT Mahasiswa Pendidikan Matematika dalam Mendesain Perangkat Pembelajaran 21st CLD - Manurung, Felisia Oktovia; Pujiastuti, Heni (Media Pendidikan Matematika, 2022)
In this era of digital revolution, education is slowly being sought to use technology in its implementation. Besides the many products that are created to support the learning process, this of course needs to be in line with the capabilities of its users, namely students, educators and prospective educators. The ability to operate technology is needed so that educational technology products that are created are effective, especially to meet the learning needs of the 21st century. Therefore, the researcher intends to research with the aim of analyzing the ICT ability of Mathematics Education students at Sultan Ageng Tirtayasa University in designing learning devices that involve technology as one of the dimensions of 21st Century Learning Design (CLD). This study uses a qualitative descriptive method by distributing a test instrument about ICT knowledge and rating scale questionnaires. This study collects information fromÂ result of test insrument, questionnaires and various supporting literature that can be used as a basis for research. Based on this, it was found that the students’ ICT abilities were on a good scale on average overall but there were still skills that didnâ€™t reach the indicators.